Emerging Challenges of Acute Bilateral Diabetic Cataract in Pediatric: Insight to Early Detection and Management– A Case Report - Valentina, Clara; Sutyawan, I Wayan Eka; Surasmiati, Ni Made Ayu; Kusumadjadja, I Made Agus; I Wayan Gede Jayanegara (Majalah Oftalmologi Indonesia, 2025)
Purpose: To report rare case of acute bilateral cataract in pediatric with Type 1 Diabetes Mellitus as ocular complication despite of good glycaemic controls and its management. Methods: A 17-year-old male patient complained of blurry vision and glare in both eyes(BE) since 3 months in newly diagnosed T1DM (HbA1c 10% --> now 6.3%). Visual Acuity (VA) was 6/45PH6/21f2, with correction S-1.50 advancing to 6/18 in BE. Slitlamp examination of BE revealed lens opacity (P3),central position, 3mm in diameter, retinometri 0.32. Posterior segment evaluation and intraocular pressure (IOP) were within normal limits. Right eye (RE) was underwent lensectomy and IOL insertion under GA. Results:  Postoperative RE with final VA of 6/18 PHNI and IOP of 43 mmHg. Patient was given antiinflammation eyedrops, oral and topical antiglaucoma, and received controlled final IOP of 8mmHg within 3 days and remain stable until now without antiglaucoma. Result was satisfying despite of uncomplicated secondary glaucoma as short-term complication that resolved with therapy. Evaluation and close monitoring postoperatively is needed and play significant role in visual outcome. Conclusions: Early detection for ocular complication in DM is needed as cataract genesis process still progressing despite of good glycaemic control. Ocular manifestation may present as early sign of undiagnosed T1DM or as its complications. Comprehensive and holistic multidicipline treatment, glycaemic control,  and routine evaluation is essential and play significant role in the success of metabolic cataract therapy and progression of microvascular complications due to DM. Lensectomy + IOL implantation still the mainstay therapy in pediatric cataract.  Awareness play vital role as it possibly cause decreased vision and or amblyopia, leading to blindness.